Legal Education as a Preventive Measure Against Sexual Violence and Bullying at SMP N 1 Temanggung - Basri, Basri; Muhammad, Fadil; Nuraini, Fadhilla; Tsabita, Azza Salma; Setyaningrum, Elsa Dwi (Borobudur Journal on Legal Services, 2025)
Sexual violence and bullying against children, especially within school environments, are serious issues that have emerged in the education sector. This community service activity is a collaboration between SMP Negeri 1 Temanggung and the Child Protection Commission (Komnas Perlindungan Anak) of Temanggung Regency. The purpose of the program is to increase awareness and understanding among teachers and students regarding issues of sexual violence and bullying against children, as well as to provide knowledge related to prevention within schools and society. The methods applied include interactive socialization, focused group discussions, and the delivery of educational materials conducted at SMP Negeri 1 Temanggung. The results of the activity include a deeper understanding among students and teachers regarding sexual violence and bullying against children. In addition, they also gained knowledge of the steps that can be taken to prevent such acts and understood how to obtain legal protection if they become victims of sexual violence and bullying.